IMPACT OF SOCIAL MEDIA ON CONSUMER BUYING PATTERN - Sundar D, Anupama; M B, Kavyashree (International Journal of Research -GRANTHAALAYAH, 2022)
Objectives: To investigate the impact of Consumer-Generated Advertising on the attitudes and behaviours of consumers for the purpose of interacting with social media features and sharing of electronic word-of-mouth. Methodology: Descriptive research methodology was adopted for the current study. A convenience sampling technique was adopted and a total of 65 responses were collected from students and working professionals. Based on the objectives of the research a structured questionnaire was designed with five points Likert scale. The data collected was analysed with the help of SPSS. Descriptive Statistics, KMO test for sampling adequacy, and Exploratory Factor Analysis were adopted for data analysis. Findings: As per the inferences gathered, it is evident that consumers perceived the video advertisements on YouTube and framed them as consumer-generated or firm-generated advertisements, for the purpose of determining the effects of the credibility of the source, with various levels of product involvement. The research results indicated, individual consumers as a source credibly enhanced the attitudes and behaviours of advertisements. Application: The study provides insights for business leaders and managers, to take the initiatives to influence consumers to develop significantly positive attitudes and behaviors towards the firm’s advertisements.